Mathematical modelling of the impact of expanding levels of malaria control interventions on Plasmodium vivax - Michael T. White (Nature Portfolio, 2018)
Plasmodium vivax poses a unique challenge for malaria elimination worldwide. Here, White et al. develop an individual-based mathematical model of P. vivax transmission and evaluate intervention strategies in Papua New Guinea.